Yinzhihuang injection as adjuvant treatment for neonatal hyperbilirubinemia: a systematic review and meta-analysis of randomized clinical trials - Li, Junqiang; Zhang, Liyu; Chen, Zhongguo; Qin, Min (Frontiers in Pharmacology, 2024)
Background: Neonatal hyperbilirubinemia (NH) is a common phenomenon for neonate inpatients, and Yinzhihuang (YZH) injection is a well-known Chinese herbal formula for the treatment of NH. This study aims to evaluate the efficacy of YZH injection on NH. Methods: A comprehensive literature search was performed in four Chinese databases [ China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature (CBM), China Science Journal Database (VIP), and Wan Fang ] and four English language databases ( PubMed, Web of Science, EMbase and the Cochrane Library ) from inception to April 16, 2024. Randomized controlled trials on YZH injection for NH were collected. Review Manager 5.4 software was used for meta-analysis and bias risk assessment.Result: Twenty-two trials involving 2714 neonates were included. Significant differences were detected between YZH injection group and control group for total effective rate (RR=1.15, 95%CI: 1.11 to 1.20, p ＜ 0.00001), serum bilirubin level (the third day,